Design of A Semi-Automatic Banana Chips Slicing Machine to Reduce Musculoskeletal Disorders (MSDS) In Workers - Aprillova, Carmelita Virry Clarissa; Ekoanindyo, Firman Ardiansyah (JTI: Jurnal Teknik Industri, 2024)
This research aims to improve the banana chip-slicing process at Aneka Keripik Clarissa'N UMKM. The slicing is done manually, leading to workers' discomfort and Musculoskeletal Disorders (MSDs). To address this, we are designing a new machine based on the Nordic Body Map (NBM) questionnaire results. This machine, tailored using workers' anthropometric data, aims to be ergonomic, reducing fatigue and enhancing comfort and efficiency in the slicing process. The goal is simplifying and speeding up production while ensuring maximum worker well-being. Keywords: Anthropometrics, MSDS, Nordic Body Map, Tool Design